Event-triggered neural network voltage control for distribution networks under actuator attacks based on observers - Zhang, Fang (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes an event-triggered neural network control approach to address the voltage control issue in distribution networks under false data injection (FDI) attacks. Firstly, a mathematical model of voltage deviation in distribution networks considering the impact of FDI attacks is established to accurately represent the dynamic behavior of the attacked system.
Keywords: distribution network; voltage control; voltage over limit; event-triggered; adaptive neural network